IGR J19308+0530: Roche lobe overflow on to a compact object from a donor 1.8 times as massive - Ratti, E.; van Grunsven, T.; Torres, M.; Jonker, P.; Miller-Jones, James; Hessels, J.; van Winkel, H.; van der Sluys, M.; Nelemans, G. (Wiley-Blackwell Publishing Ltd., 2013)
We present phase-resolved spectroscopy and photometry of the optical counterpart to the X-ray binary IGR J19308+0530. Ellipsoidal modulations in the light curve show that the F-type companion star in the system is Roche lobe filling. The optical spectra are dominated by absorption features from the donor star, with ~10–20 per cent disc contribution to the optical continuum. We measure an orbital period of 14.662 ± 0.001 h, a radial velocity semi-amplitude for the companion star of K2 = 91.4 ± 1.4 km s− 1 and a rotational broadening of v sin i = 108.9 ± 0.6 km s− 1. From K2 and v sin i, given that the donor star is filling its Roche lobe, we derive a mass ratio of q = M2/M1 = 1.78 ± 0.04, which is typically considered to be too large for stable Roche lobe overflow. Our observations support an inclination of ~50°. The accretor in IGR J19308+0530 is most likely a white dwarf, although a neutron star cannot entirely be excluded.